1996
DOI: 10.1177/106591299604900409
|View full text |Cite
|
Sign up to set email alerts
|

When Waves Collide: Cycles of Protest and the Swiss and American Women's Movements

Abstract: This article makes two related arguments. First, a rising cycle of protest may influence existing movements by altering their tactics, providing new allies, and altering others' perceptions of the movements. I illustrate these effects with examples drawn from the Swiss women's movement. The Swiss women's movement is unique because the first wave was still pursuing the enfranchisement of women when the second wave mobilized in the 1960s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…A few reasons can be mentioned for these developments (Linder , 60–2). First, although the Swiss women's movement was not generally weaker than its European and American counterparts (Banaszak , 840–41), it lost momentum after the unsuccessful push for women's suffrage in the 1920s. Moreover, like the women's movements of many other European countries (Beckwith , 446; Rucht , 261), it relied on education and referendum campaigns instead of more confrontational tactics that could have been more successful (Banaszak , 148–85).…”
Section: Women's Political Representation In Switzerlandmentioning
confidence: 99%
“…A few reasons can be mentioned for these developments (Linder , 60–2). First, although the Swiss women's movement was not generally weaker than its European and American counterparts (Banaszak , 840–41), it lost momentum after the unsuccessful push for women's suffrage in the 1920s. Moreover, like the women's movements of many other European countries (Beckwith , 446; Rucht , 261), it relied on education and referendum campaigns instead of more confrontational tactics that could have been more successful (Banaszak , 148–85).…”
Section: Women's Political Representation In Switzerlandmentioning
confidence: 99%
“…Although both democratic theory and empirical evidence suggest that groups can achieve positive substantive policy representation through descriptive representation, some scholars have suggested that there may be a backlash, or negative reaction, as a politically marginal group achieves social, economic, or political gains (Blalock 1967;Bratton 2002;Cammisa and Reingold 2004;Studlar and McAllister 2002;Yoder 1991). For example, many researchers have argued that the women's movement, while accomplishing many significant goals in the 1970s, created a backlash of antiwoman, or at least antifeminist, sentiment in the 1980s (Banaszac 1996;Faludi 1991;Haas-Wilson 1993;Thomas 1994;Yoder 1991). In fact, Bratton (2002) found that an increase in the number of female state legislators is associated with a legislative backlash.…”
Section: Descriptive Representation and Backlashmentioning
confidence: 99%
“…The so-called Brunner affair reverberated across the political stage, affecting women's descriptive representation in most of the political parties as well as their engagement and their substantive success. In the aftermath, women from “all political parties created a shadow council called the Frauenbundesrat , which demanded a 50% quota for Nationalrat seats” (Banaszak 1996, 853). By the 1995 election, women's membership in the Ständerat had doubled, and the SPS had adopted a 50% quota for female candidates.…”
Section: Swiss Politics and Gendermentioning
confidence: 99%